14‐3‐3 Proteins regulate K2P5.1 surface expression on T lymphocytes. (27th November 2016) - Fernández‐Orth, Juncal; Ehling, Petra; Ruck, Tobias; Pankratz, Susann; Hofmann, Majella‐Sophie; Landgraf, Peter; Dieterich, Daniela C.; Smalla, Karl‐Heinz; Kähne, Thilo; Seebohm, Guiscard; Budde, Thomas; Wiendl, Heinz; et al.
Abstract : K2P 5.1 channels (also called TASK‐2 or Kcnk5 ) have already been shown to be relevant in the pathophysiology of autoimmune disease because they are known to be upregulated on peripheral and central T lymphocytes of multiple sclerosis (MS) patients. Moreover, overexpression of K2P 5.1 channels in vitro provokes enhanced T‐cell effector functions. However, the molecular mechanisms regulating intracellular K2P 5.1 channel trafficking are unknown so far. Thus, the aim of the study is to elucidate the trafficking of K2P 5.1 channels on T lymphocytes. Using mass spectrometry analysis, we have identified 14‐3‐3 proteins as novel binding partners of K2P 5.1 channels. We show that a non‐classical 14‐3‐3 consensus motif (R‐X‐X‐pT/S‐x) at the channel's C‐terminus allows the binding between K2P 5.1 and 14‐3‐3. The mutant K2P 5.1/S266A diminishes the protein‐protein interaction and reduces the amplitude of membrane currents. Application of a non‐peptidic 14‐3‐3 inhibitor (BV02) significantly reduces the number of wild‐type channels in the plasma membrane, whereas the drug has no effect on the trafficking of the mutated channel. Furthermore, blocker application reduces T‐cell effector functions. Taken together, we demonstrate that 14‐3‐3 interacts with K2P 5.1 and plays an important role in channel trafficking. Abstract : K2P 5.1 channels possess a putative non‐classical consensus motif for 14‐3‐3 proteins that mediates the interaction and promotes K2P 5.1 channels to the plasma membrane. An amino acid mutation reduces the binding of 14‐3‐3 proteins to K2P 5.1 resulting in a reduced number of channels at the plasma membrane and a decreased potassium efflux. Pharmacological inhibition of 14‐3‐3 protein binding to K2P 5.1 functionally impacts T‐cell proliferation and cytokine production. 14‐3‐3 proteins may represent a pharmacological target for the treatment of multiple sclerosis and other autoimmune diseases.